Hybrid rhyolitic eruption at Big Glass Mountain, CA, USA - Castro, Jonathan; Walter, Sebastian C. (Volcanica, 2021)
Eruptive dynamics of the 1060 CE rhyolitic eruption of Big Glass Mountain (BGM), USA, are investigated with field observations, hydrogen isotope and H2O content analysis of pyroclastic obsidian chips and lavas. Field relations at BGM reveal evidence for hybrid eruption, defined as synchronous explosive venting and effusive emplacement of vast obsidian lava flows. This activity is particularly well manifested by extensive breccia zones implanted within the BGM obsidian lavas, which may represent rafted tephra cones, in addition to remnants of airfall tephra on the lava. Rhyolitic obsidians collected from a 2.5-m-thick fall deposit and co-eruptive lava flow were studied by FTIR and TCEA methods to elucidate the eruption’s degassing history. The data, along with VolcDeGas program simulations, demonstrate a correlation between H2O content and H-isotopic composition (δD) that likely reflects ever-increasing amounts of volatile loss via repetitive close-system steps, best described as batched degassing.